1974
DOI: 10.1111/j.1365-3180.1974.tb01047.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and control of blackberry (Rubus fruticosus L. agg.) II. Reproduction*

Abstract: Summary: Résumé: Zusammenfassung The reproduction of blackberry (Rubus fruticosu L. agg.) is described with particular reference to R. procerus P.J. Muell. Reproduction is by seed, rooting at cane apices, suckering of lateral roots, and from pieces of roots and canes. In Victoria, Australia, R. procerus occurs mainly in non‐agricultural land and neglected pastures and is rare in well‐managed pastures and crops. This is attributed to the poor establishment of seedlings and the ease with which rooting at cane ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 14 publications
(7 reference statements)
0
34
0
Order By: Relevance
“…In one study, its seedlings failed to establish in areas with less than 44% of sunlight (Amor 1974).…”
Section: Historymentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, its seedlings failed to establish in areas with less than 44% of sunlight (Amor 1974).…”
Section: Historymentioning
confidence: 99%
“…Most blackberries require warm (20 to 308C) stratification for 3 months followed by cold (2.2 to 58C) stratification for the next 3 months (Cal-IPC 2013;Hoshovsky 2000). Only 7Á10% of seeds in soil are viable, usually germinating after 2 yr (Amor 1974). Brunner et al (1976) suggested that Himalayan blackberry seeds excreted by foxes had up to 30% higher germination compared with seeds that did not pass through the foxes' digestive system.…”
Section: Reproductionmentioning
confidence: 99%
“…in late summer (Canada: Hamer and Herrero 1987;Hamer et al 1991;McLellan and Hovey 1995, Alaska: Stelmock and Dean 1986, Spain: Clevenger et al 1992, France: Berducou et al 1983, Norway: Elgmork and Kaasa 1992. Some Rubus species are typical pioneer plants that rapidly invade forest gaps and cleared areas (Amor 1974;Suzuki and Maeda 1981;Suzuki 1987). As the forests in the study area were logged on a large scale in the early 1970s (Miura 1999), it is plausible that Rubus species invaded the clearings and spread.…”
Section: Comparison Of Dietsmentioning
confidence: 99%
“…Our calculation for seedling recruitment was based on the assumption that all seedlings germinated from seeds produced during the previous year and not from the seed bank. This assumption was probably reasonable based on the rapid disappearance of Rubus seeds from the soil due to predation (Maxwell 1990;Kollmann et al 1998) and the low germination probability of seeds following storage (Amor 1974) or desiccation in the field (S. Lambrecht-McDowell, personal observation).…”
Section: Demographic Analysesmentioning
confidence: 99%
“…Control methods that involve mowing canes or applying herbicide to foliage have proven relatively ineffective at controlling this species (reviewed in Hoshovsky 2001), probably because such methods have failed to adequately affect allocation to the belowground portions of the plant. The most effective controls for this invasive Rubus include the introduction of animals that graze canes to the roots from which cane v sprout (Amor 1974;Daar 1983) or the use of herbicides applied to cut or burned stems following fruit set (Hoshovsky 2001). The effectiveness of this latter approach is likely due to the translocation of nutrients and, therefore, herbicides from reproductive canes to the roots prior to senescence.…”
Section: Control Of R: Discolormentioning
confidence: 99%